The new approach for some coupled fixed point results - Yolacan, Esra; Kızıltunc, Hükmi (Communications in Mathematics and Applications, 2017)
The aim of this paper is to stand for new approach of the results of Jain et al. and Berinde. The proofs of all our results are without mixed monotone property. An example are also given to confirm the effectiveness of the presented work.